Individual Surgical Treatment of Stage IV Müller-Weiss Disease According to CT/MRI Examination: A Retrospective Study of 12 Cases - Liu, Wenzhou; Chen, Yanbo; Zeng, Gang; Yang, Tao; Ma, Mengjun; Song, Weidong (Frontiers in Surgery, 2022)
Background This study reported the individual surgical treatment of 12 cases with stage IV Müller-Weiss disease (MWD) according to CT/MRI examination. Methods In total, 12 cases diagnosed with stage IV MWD in our hospital from 2015 to 2019 were included in the retrospective study. Relevant clinical outcomes were evaluated preoperatively and postoperatively. Results The follow-up results showed satisfactory outcomes in all cases. All the cases were presented with tenderness and chronic pain on the midfoot dorsum, and three cases were also presented with tenderness and pain on the lateral side of the midfoot, in which calcaneal cuboid arthritis was revealed by CT/MRI. The American Orthopedic Foot and Ankle Society (AOFAS) scores elevated from 62.5 ± 6.8 (range: 53–74) preoperatively to 95.3 ± 7.2 (range: 73–100) postoperatively (P < 0.005). The Visual Analog Scale (VAS) scores declined from 4.2 ± 0.9 (range: 3–5.5) preoperatively to 0.5 ± 0.3 (range: 0–2) postoperatively (P < 0.001). On the weight-bearing lateral view of the foot, the Tomeno-Méary angle (TM lat) changed from −11.2 ± 4.2 (range: −17.2 to −2.8) degrees preoperatively to −2.4 ± 3.9 (range: −10.2 to 5.2) degrees postoperatively (P < 0.001). Conclusions The fusion of the talus-navicular joint and the adjacent affected joint provide good clinical outcomes. The CT/MRI scans are helpful to identify the adjacent joint arthritis and provide indications for individual treatment for Stage IV MWD.